PTU-046 Prospective comparison of emr vs esd in barrett's neoplasia: are we too afraid of knives in the oesophagus?. (22nd June 2015) - Chedgy, FJQ; Bhattacharyya, R; Kandiah, K; Basford, P; Bhandari, P
Abstract : Introduction: Use of ESD in the Western setting is limited to a few centres with limited numbers of cases, due to concerns regarding complication rates and no established training pathway. The risks of ESD in the oesophagus are perceived to be high and the consequences disastrous. For this reason, endoscopic mucosal resection (EMR) is the most common technique used to resect early Barrett's cancer. The drawback of EMR is piecemeal resection and poor interpretation of histology. Method: We report our experience of oesophageal ESD in 51 cases and compare our data for EMR (140 cases) over the same period. Results: 51 ESD resections for Barrett's neoplasia were performed between 2006 and 2014. 140 EMR's were performed in the same period. Mean age 71 years for ESD group and 75 for EMR group. All procedures were undertaken by a single expert endoscopist (PB). Table 1 shows patient characteristics and lesion characteristics. The endoscopic cure rate in the ESD group was 83% and the EMR group was 82%. It took a mean of 1.2 procedures in the ESD group and 1.4 procedures in the EMR group. In the ESD group there was a recurrence rate of 3%, in the EMR group 16%. Additional radiofrequency ablation was required in 17% of patients in the ESD group and 34% of patients in the EMR group. There was one perforation in the ESD group which was successfully managed conservatively with endoclips, not requiring surgery. There were 4 cases of bleeding and 3 cases of stricturing managed endoscopically in the EMR group. Conclusion: ESD for Barrett's neoplasia is feasible, safe and effective in Western hands. Our lesion selection data shows that ESD is being used mainly for nodular lesions and cancerous lesions as compared to EMR for flat and non-cancerous lesions. Neoplasia recurrence is higher in EMR vs ESD. This calls for a randomised controlled trial comparing EMR vs ESD for the resection of nodular lesions in Barrett's neoplasia. Disclosure of interest: None Declared.